Social Media Engagement and Academic Performance of University Scholars (Victoria Journal of Management, 2025)
Social media engagement is indispensable for learning, sharing, knowledge development, and communication approaches for academics and students that enhance internal skills and capacity for social behavior. The study’s primary goals are to investigate how university students’ use of social media affects their academic achievement. The study adopted a descriptive research design. This study used primary sources of data. The data were collected by distributing the questionnaire through online and physical forms using convenience sampling techniques. The findings of the research revealed an influence of social media on academic performance. It showed that social media enhances connectivity and information sharing, reflecting its impact on university students, which requires digital literacy, responsible use, and maintaining a healthy balance between online engagement and academic pursuits. The findings of the study can be useful for policymakers, social media service providers, and other stakeholders to craft a strategic framework.